1984
DOI: 10.1085/jgp.84.2.265
|View full text |Cite
|
Sign up to set email alerts
|

A monoclonal antibody to guanine nucleotide binding protein inhibits the light-activated cyclic GMP pathway in frog rod outer segments.

Abstract: A monoclonal antibody that blocks the light-activated cyclic GMP (cGMP) pathway in frog photoreceptor outer segments (ROS) has been obtained . The antibody (4A) inhibits guanine nucleotide binding to G-protein, the intermediate that links rhodopsin excitation to cGMP phosphodiesterase (PDE), inhibiting light-induced PDE activity as a consequence . Antibody inhibition of the light-activated cGMP pathway is complete at a stoichiometry of approximately one antibody per G-protein in the mixture, which indicates hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1984
1984
1992
1992

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…Incubation of squid photoreceptor membranes with the monoclonal antibody 4A before incubation had no effect on light-induced binding activity (results not shown). This is in contrast with the frog photoreceptor where antibody 4A inhibits 90 % of the light-induced GTP[S] binding (Hamm & Bownds, 1984). However, incubation of squid photoreceptors with pertussis toxin in the dark for 1 h eliminates 50 % of the light-induced binding ( Table 2).…”
Section: Toxin and Antibody Effects On Nucleotide Bindingmentioning
confidence: 92%
See 1 more Smart Citation
“…Incubation of squid photoreceptor membranes with the monoclonal antibody 4A before incubation had no effect on light-induced binding activity (results not shown). This is in contrast with the frog photoreceptor where antibody 4A inhibits 90 % of the light-induced GTP[S] binding (Hamm & Bownds, 1984). However, incubation of squid photoreceptors with pertussis toxin in the dark for 1 h eliminates 50 % of the light-induced binding ( Table 2).…”
Section: Toxin and Antibody Effects On Nucleotide Bindingmentioning
confidence: 92%
“…The protein bands of unstained gels were electroblotted overnight on to nitrocellulose paper (Towbin et al, 1979). Nitrocellulose strips were then treated with either control serum or monoclonal antibody 4A, which was raised in the mouse against the a subunit of bovine transducin (Hamm & Bownds, 1984). Immunoreactivity was revealed using an immunoperoxidase procedure (Vectastain ABC kit; Vector Labs, Burlingame, CA, U.S.A.) based on biotinylated secondary antibodies and a horseradish-peroxidase-labelled avidin-biotin complex.…”
Section: Western Blotsmentioning
confidence: 99%
“…The doublet nature of peripherin has been previously shown and the 66-68-kD protein may be a result of incomplete disulfide bond cleavage . Western blots of disk and plasma membrane labeled with specific monoclonal or polyclonal antibodies indicated that the 48-kD protein or S-antigen was present in very low quantities in the disk and plasma membrane fractions, whereas the ct subunit of the G-protein (Hamm and Bownds, 1984) was absent in the disks but present in the plasma membrane.…”
Section: Anti-rhodopsin and Anti-peripherin Binding To Disk And Plasma Membranesmentioning
confidence: 99%
“…The results to date have shown that antibodies to ROS proteins can successfully be used to identify the molecular weights and to localize the proteins in isolated ROS. Use of antibodies in inhibiting one light-dependent reaction, G-protein activation by light, is described in the accompanying paper (Hamm and Bownds, 1984). Additional antibodies will be generated by the methods described here and applied to further studies of the phototransduction pathway.…”
Section: Discussionmentioning
confidence: 99%